Arctic drainage of Laurentide Ice Sheet meltwater throughout the past 14,700 years - Süfke, Finn; Gutjahr, Marcus; Keigwin, Lloyd D.; Reilly, Brendan; Giosan, Liviu; Lippold, Jörg (Communications earth & environment, 2022)
During the last deglaciation substantial volumes of meltwater from the decaying Laurentide Ice Sheet were supplied to the Arctic, Gulf of Mexico and North Atlantic along different drainage routes, sometimes as catastrophic flood events. These events are suggested to have impacted global climate, for example initiating the Younger Dryas cold period. Here we analyze the authigenic Pb isotopic composition of sediments in front of the Arctic Mackenzie Delta, a sensitive tracer for elevated freshwater runoff of the retreating Laurentide Ice Sheet. Our data reveal continuous meltwater supply to the Arctic along the Mackenzie River since the onset of the Bølling-Allerød. The strongest Lake Agassiz outflow event is observed at the end of the Bølling-Allerød close to the onset of the Younger Dryas. In context of deglacial North American runoff records from the southern and eastern outlets, our findings provide a detailed reconstruction of the deglacial drainage chronology of the disintegrating Laurentide Ice Sheet.
Gesehen am 24.05.2022